Law of the Sea : Selected Writings. - Vukas, Budislav (Brill Academic Publishers, 2004)
These collected essays reflect the development of the author's views as well as the evolution of the law of the sea itself since the beginning of the Third United Nations Conference on the Law of the Sea. After an introductory chapter, the author, Judge at the International Tribunal for the Law of the Sea in Hamburg, describes and analyzes topics such as the sources of the law of the sea, the relation of the law of the sea to other fields of international law, maritime delimitation, natural resources and navigation, as well as military uses of the sea, the protection of marine environment, enclosed and semi-enclosed seas and the settlement of disputes. The papers reproduced in this volume (some of which in French) will be of interest to both academics and professionals interested in the law of the sea and its institutions.